Microbial dynamics in industrial blue veined cheeses in different packaging. (May 2016) - Duval, P.; Chatelard-Chauvin, C.; Gayard, C.; Rifa, E.; Bouchard, P.; Hulin, S.; Picque, D.; Montel, M.C.
Abstract: The aim of this study was to evaluate the effects of packaging on the microbiota of blue veined cheeses. The microbial dynamics of portions of industrial cheeses packaged under vacuum in different films and whole cheeses in aluminium foil was compared using culture-dependant and metagenomic approaches. There was no oxygen in the packaging and CO2 concentrations were between 5 and 12%. The composition of the lactic acid bacteria population did not change significantly during storage; it varied more according to factory of origin. Vacuum packaging hampered the growth of aerobic bacteria ( Brevibacterium, Arthrobacter, Brachybacterium) and Gram-negative bacteria more than did stretch film. In vacuum-packed cheese portions, Staphylococcus and/or Brevibacterium and Arthrobacter were the dominant Gram-positive catalase-positive populations, depending on the factory of origin. Cheese packaged under vacuum had a lower pH than cheese in aluminium foil or stretch film.